Optical Properties of Te Thin Films Prepared by Thermal Evaporation Technique - Hachim, Fatin G. (University of Thi-Qar Journal of Science, 2019)
This work describes, Tellurium (Te) films were deposited on glass substrates at room temperature by the method of vacuum evaporation with thickness (0.4μm), with rate of deposition equal to (5.5Å/sec), the samples are annealed in a vacuum for one hour at (373 and 433) K. The optical properties such as absorption coefficient () was determined using the absorbance and transmittance measurement from FTIR Shimadzu spectrophotometer, with range of wave length (2800-3900) nm. And also calculated optical constants (refractive index (n), extinction coefficient (k)) for Tellurium films. The tests have been shown that the optical energy gap increases with increasing of annealing temperature for the samples